Hubungan Dukungan Sosial Keluarga Dengan Kesepian Lansia di Kota Batam - Yulia Devi Putri (Jurnal Keperawatan Muhammadiyah, 2021)
Objective:  to find out the relationship between family social support and loneliness elderlyMethods: This article is a type of correlation research with a Cross Sectional Study approach.  The data analysis method used in this study is the correlation method of correlation analysis.  To measure the relationship between two variables, namely the independent variable and the dependent variable. To test the hypothesis in this study, the Spearman range correlation test was used.Results:  The results showed that the elderly who experienced moderate loneliness were 78.68%  and the elderly who received moderate family social support 84.27%. From the results of research that has been conducted on 50 people who have experienced loneliness in the working area of Tanjung Sengkuang Health Center in 2012, the correlation strength value (r) = - 0.247, significant value (p) = 0.039. The results of this study show that there is a negative, weak and significant relationship between family social support and loneliness in the elderlyConclusion:  From the correlation test, the KD value = 7.2% means that family social support contributes 7.2% to loneliness while 92.8% is influenced by other factors.